Transformative leadership and its rolein the development of job immersion from the point of view of sports education teachers in Diyala province - Mahmoud Shahadeh, Osman (International Journal of Psychosocial Rehabilitation, 2020)
For the purpose of identifying the role of transformative leadership school principals in Diyala province by the functional immersion of sports education teachers, the researcher used the descriptive curriculum in a survey method on a sample of (3,19) teachers selected in a random manner, after distributing the two measures of research to them and collecting data and processing it statistically to obtain the desired results The researcher reached the most important conclusion: there is an expulsive relationship between transformational leadership and immersion, and one contributes to the improvement of the other.